PENGARUH DAYA HISAP TERHADAP ALAT SUCTION PUMP - Iqbal Eka Riansyah; Hotromasari Dabukke (JURNAL MUTIARA ELEKTROMEDIK, 2021)
Research on the effect of suction power on the YB-DX23B smaf suction pump has been carried out.The method used in this research is quantitative experiment by measuring, testing and collecting data directly on the suction pump. The measuring instrument used is Vacum Gauge Meter. By using water as an object to replace blood and with a predetermined 10 second timer set, set the volume to adjust the volume of water you want and set the regulator to adjust how much suction power is needed.This research was conducted at the Electronics Laboratory of Sari Mutiara University- Indonesia. The results of this research are when the regulator is set at parameter -100 mmHg, the output on the vacuum gauge meter becomes -10 cmHg and the liquid is inhaled as much as 700 ml, when the regulator is set at parameter -200 mmHg, the output on the vacuum gauge meter becomes -20 cmHg and the liquid is inhaled as much as 1000 ml, when the regulator is set at the parameter -300 mmHg, the output on the vacuum gauge meter becomes -30cmHg and the liquid sucked is 1300 ml, and the regulator is set to the parameter -400 mmHg and the output on the vacuum gauge meter becomes -40 cmHg and the liquid is inhaled as much as 1500 ml.Measurements using a vacum gauge on the suction pump according to the settings set by the user. The greater the vacuum power, the faster the process of suctioning thevolume of liquid in.